EVALUASI PEMILIHAN REKAN TOLL MANUFACTURING DALAM PENGEMBANGAN PRODUK OBAT GENERIK INJEKSI MEROPENEM DI SEBUAH PERUSAHAAN FARMASI DI JAKARTA - Maria Yulyana Tukan (Universitas Mercu Buana, 2015)
Abstract. A pharmaceutical company at Jakarta developed a generic meropenem sterile dosage form by toll manufacturing business cooperation with another pharmaceutical company. During the process of partner selection, there was a time delay. The target plan was 4 months but in reality it took 12 months. This research evaluates factors which cause the time delay. One of the causes was the unavailability of pre-selection model. This research test a qualitative pre-selection model using variables of management, availability oftransport choices, value added services, rate profile and quality services, service characteristics and performance measurements. The six variables described into 36 dimensions and indicators. The model tested to 10 pharmaceutical companies with sterile production facility needed for production of meropenem sterile dosage form. Research method used is qualitative descriptive analysis with searching data method through observational study. The data source is secondary data. Based on the research result, timedelay was caused by several factors related to product, procedure, quality and fee. The tested pre-selection model can be used as an alternative solution to avoid future time delay in toll manufacturing partner selection.Keywords : pre-selection, toll manufacturing, pharmaceutical